The essence of accommodating older adults into the social care sector in Malaysia - Minhat, Halimatus Sakdiah; Mat Din, Hazwan; Raja Adnan, Raja Nurzatul Efah (Tech Science Press, 2021)
Population ageing puts pressure on the workforce and increase the demands for aged workforce. The demographic shifts have made the issue of healthier workers, especially those of advanced age and physically related job scopes, a fundamental aspect to employing older workers. Hence, this study aimed to explore the best practices to employ older adults into the social care sector. The social care sector was chosen in view of the nature of job and declining demand among younger workers. A qualitative study was conducted involving series of focus group discussions (FGD) with social care workers of long-term care centers in the peninsular Malaysia. Data was collected using a validated and pre-tested semi-structured interview protocol. Each focus group discussions and in-depth interviews were lasted between 45 min to 1 h. A total of 57 workers were consented for the study which was divided into young and old workers based on the mean age of 41.43 [SD ± 9.97] years old. The content of the interviews was transcribed verbatim and thematic analysis was performed to inductively identify the coding and themes within the data related to the challenges employing older workers into the social care sector. Three categories of coding were identified (individual, environmental and management factors), leading to the identification of two important themes which are healthy workplace and work autonomy. The findings indicate the needs for work culture transformations to cultivate healthy working environment and freedom of speech particularly among the older workers.